Leading lady : a memoir of a most unusual boy - Busch, Charles (Smart Pop Books, an imprint of BenBella Books, Inc., 2023)
"Full of humor and heart, and including 16 pages of photographs, Leading Lady is perfect for theatre fans new and old, as well as anyone who knows the joy of finally finding the craft that makes their soul sing"--